FERGANA VALLEY CLIMATIC SUITABLE, NEW VARIETIES OF MULBERRY WELD SWORDNGAN GROWTH AND BRUISING OF SEEDLINGS VA STUDY OF LEAF FORMATION (Academicia Globe: Inderscience Research, 2026)
In this scientific work, the issues of propagating promising mulberry varieties by vegetative methods, namely by bud grafting, were studied.